2016
DOI: 10.1021/jacs.6b04529
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Au/δ-MoC and Cu/δ-MoC Catalysts for the Conversion of CO2: The Metal/C Ratio as a Key Factor Defining Activity, Selectivity, and Stability

Abstract: The ever growing increase of CO 2 concentration in the atmosphere is one of the main causes of global warming. Thus, CO 2 activation and conversion towards valuable added compounds is a major scientific challenge. A new set of Au/δ-MoC and Cu/δ-MoC catalysts exhibits high activity, selectivity, and stability for the reduction of CO 2 to CO with some subsequent selective hydrogenation towards methanol. Sophisticated experiments under controlled conditions and calculations based on density functional theory have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
155
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 64 publications
6
155
2
Order By: Relevance
“…Nevertheless, despite the great efforts in CO 2 reduction for CO generation, the number of catalysts with the required excellent performance under mild and convenient conditions remains limited . Noble metals, such as Pt, Pd, and Ir, are commonly used for CO 2 conversion,, but high cost constrains their application in large‐scale processes; therefore, the search for nonprecious metal catalyst alternatives is ongoing. Recently, Chen and co‐workers developed an effective catalyst composed of cobalt‐modified molybdenum carbide (Co–Mo 2 C), which can efficiently decompose stable CO 2 with a conversion of 9.5 % at 573 K .…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, despite the great efforts in CO 2 reduction for CO generation, the number of catalysts with the required excellent performance under mild and convenient conditions remains limited . Noble metals, such as Pt, Pd, and Ir, are commonly used for CO 2 conversion,, but high cost constrains their application in large‐scale processes; therefore, the search for nonprecious metal catalyst alternatives is ongoing. Recently, Chen and co‐workers developed an effective catalyst composed of cobalt‐modified molybdenum carbide (Co–Mo 2 C), which can efficiently decompose stable CO 2 with a conversion of 9.5 % at 573 K .…”
Section: Figurementioning
confidence: 99%
“…There have been contradictory reports regarding the molybdenum‐carbon phase behavior throughout literature. These include reports of orthorhombic, cubic, and hexagonal molybdenum carbides with differing stoichiometries . In this study, we examine two phases of molybdenum carbide—a cubic MoC phase and a hexagonal Mo 2 C phase.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difficulty in synthesizing cubic‐phase MoC, some studies have shown that it can be used as an effective catalyst or catalyst support. Posada‐Perez et al describes a set of Au/MoC and Cu/MoC materials which exhibit high activity, selectivity, and stability toward the reduction of CO 2 to CO. A theoretical study by Kunkel et al, found that cubic MoC exhibits promising behavior for activating CO 2 along with TMCs such as ZrC, TaC, NbC, HfC, and TiC. The activity of cubic MoC for cyclohexene hydrogenation is reported to be comparable to that of group 8‐10 metals .…”
Section: Introductionmentioning
confidence: 99%
“…Study of gas-phase reactions that can be performed under isolated conditions is important to understand heterogeneous catalysis at a strictly molecular level [1][2][3][4][5][6][7]. Gold catalysis is an appealing research topic in gasphase studies because highly dispersed gold catalysts are being actively studied since the breakthrough [8,9] that TiO 2 supported gold nanoparticles can catalyze CO oxidation at low temperatures, and supported gold exhibits extraordinary catalytic activity in many other chemical processes [10][11][12][13][14]. Gold-containing heteronuclear metal oxide clusters (HMOCs) [15] are promising models to explore the nature of oxide supported gold catalysis.…”
Section: Introductionmentioning
confidence: 99%